White Columns Update 1986 - 87. (New York : White Columns, 1987)
Kidd, Julia ; Brill, John ; Hsaio, Gilbert ; Corriss, Michael ; Laramée, Eve ; Busto, Ana ; Wild Mouse Art ; Brazelton, Tom ; Andoe, Joe ; Wasow, Oliver ; B Tisdale, Daniel ; Zoller, John ; Mitchell, Curtis ; Morgan, Robert ; Estridge, Larry ; Wagner, Sokhi ; Mc Cabe, Sigrid
White Columns Up Date 1986 - 87, White Columns, New York, May 29 - June 20, 1987
boek